String theory - Polchinski, Joseph Gerard. (Cambridge University Press, 2005)
This is an impressive book. It is notable for its consistent line of development and the clarity and insight with which topics are treated . . . It is hard to think of a better text in an advanced graduate area, and it is rare to have one written by a master of the subject. It is worth pointing out that the book also contains a collection of useful problems, a glossary, and an unusually complete index.’